2013 ESC GUIDELINES ON THE MANAGEMENT OF STABLE CORONARY ARTERY DISEASE - Gilles Montalescot; Udo Sechtem; Stephan Achenbach; Felicita Andreotti; Chris Arden; Andrzej Budaj; Raffaele Bugiardini; Filippo Crea; Thomas Cuisset; Carlo Di Mario; J. Rafael Ferreira; Bernard J. Gersh; et al. (Российский кардиологический журнал, 2014)
.